Precision control of kerf in metal cutting using dry micro WEDM: issues and challenges - Ali, Mohammad Yeakub; Banu, Asfana; Abd. Rahman, Mohamed; Hazza Faizi Al Hazza, Muataz; Adesta, Erry Yulian Triblas (Trans Tech Publications Ltd., 2018)
Micro dry wire EDM is a process where gas is used as the dielectric fluid instead of a liquid. In this process certain modifications of a wire EDM are needed during the machining operation to achieve stable machining. Optimizing kerf to get high dimensional accuracy is one of the critical issues in micro dry wire EDM. The fundamental modelling for optimum kerf using micro dry wire EDM has not been formulated yet. Due to the complex phenomenon, the prediction of optimum kerf in a micro dry wire EDM process is rather difficult. Hence, the main objectives of this research are to improve the micro dry wire EDM process and to develop mathematical models for optimum kerf using micro dry wire EDM. During the process improvement of micro dry wire EDM, various machining setup will be involve in order to achieve the most stable process. The most stable machining process will be used to prove the developed mathematical models. A mathematical relationship between kerf and process parameters is anticipated. The mathematical models in conjunction with experimental data will eventually produce the desired theory. The developed process and mathematical model of kerf is a breakthrough in fabricating products such as micro tools, molds etc. with optimum kerf and high dimensional accuracy. The successful completion of this research will contribute to the environmental friendly micromachining process.